Effect of Beetroot Extract (Beta vulgaris L) and CMC (Carboxyl Methyl Cellulose) Concentration on Ice Cream Quality - Chairuni AR; Putri Meutia Sari; Rusnaini Rusnaini (Universitas Serambi Mekkah, 2019)
Red beet is rich in vitamin B1, B2, B3 and B6, folic acid, fiber and sugar, caloric value of red beets is still relatively moderate. To get healthy ice cream, it is generally done by adding beet extract which serves to protect blood vessels and the heart. Beet is potential to maintain the stability and reduce the blood pressure. The purpose of this study was to determine the effect of pasta for beets on the organoleptic and antioxidant properties of ice cream. This research was conducted using factorial randomized block design (RBD) consisting of 2 factors with 3 levels, namely factor I concentration of beet extract (B), B1 = 10%, B2 = 20% and B3 = 30%, factor II concentration CMC (C), C1 = 0%, C2 = 0.5% and C3 = 1%. The parameters analyzed were viscosity, overrun, melting speed and organoleptic tests (color, texture, taste and aroma). The best treatment at beetroot extract concentration of 20% and CMC concentration of 0.5% (B2C2) produced good quality beetroot ice cream with physical properties were viscosity 5830.7 cp, overrun 4.60%, melting speed 8.33 minutes and organoleptic texture test 4.03 (like ), color 4.17 (like) and taste 4.17 (like) and aroma 4.00 (like).